The causality relationship between final energy consumption, economic growth, and carbon dioxide emission from energy combustion in Indonesia - Nugraha, Andhyka Tyaz (2020)
The purpose of this study is to explore the causal linkage between final energy consumption, economic growth, and CO2 emissions in Indonesia. This study uses the annual data of Indonesia over the period 1971-2014. Data series of final energy consumption and CO2 emissions from energy combustion obtained from the International Energy Agency (IEA), while data series of the real Gross Domestic Product (GDP), the real gross domestic product (GDP) per capita, as well as the valueadded of three main development sectors collected from World Development Indicators (World Bank). The Autoregressive Distributed Lag (ARDL) technique and the Granger causality test are applied in this study. This study generated several empirical findings. First, sectoral economic growth significantly influenced total final energy consumption in Indonesia, while sectoral final energy consumption did not significantly influenced economic growth in Indonesia. In the industry sector, final energy consumption and economic growth did not have relationship, but they have a causal relationship with CO2 emissions. In the agriculture sector, economic growth has a significant impact on final energy consumption and CO2 emissions, while final energy consumption and CO2 emissions only have a short-run causal relationship. In the service sector, economic growth did not have influences on final energy consumption and CO2 emissions, while final energy consumption and CO2 emissions have a short-run causal relationship. In the residential sector, final energy consumption has a long-run relationship to economic growth and has a short-run causal relationship to CO2 emission, while residential economic growth only has a short-run effect on CO2 emission. Based on these findings, the policymakers expected to implement strategy and policy that considering conditions, situations, and challenges in those sectors, respectively. Moreover, all final energy users expected to use the new and renewable energy sources in order to reduce CO2 emission from energy combustion in Indonesia.